An Analytical Study The Art of Figurative Language in Moana : An Analytical Study - Luh Wayan Ayanti; Ni Nyomen Deni Ariyaningsih (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This analysis explores the utilization and impact of various forms of figurative language in the script of the movie